Performance of Agricultural Extension Workers in Implementing Urban Agriculture Programs in Banyumanik District, Semarang City, Indonesia - Agus Subhan Prasetyo; Anisa Nurina Aulia; Agung Sebastian Sinaga (Publisher of Widyagama University of Malang (UWG Press), 2020)
Urban farming is one of the alternatives to eliminate the impacts of the conversion of agricultural land. However, implementing urban farming activities requires various preparations, including the role of agricultural extension workers. The extension worker can make significant contributions to raise public awareness of the importance of urban farming. This study determines the performance level of extension workers in the preparation, implementation, and evaluation of urban farming extension programs in BPP Kramas, Banyumanik district. This research employed a descriptive analysis approach by using a Likert scale. The results indicate that the performance level of extension workers in extension preparation, extension implementation, evaluation, and reporting are in the high category, with an average percentage achievement of 96%. It means that the urban farming program in Kramas Banyumanik district had been done well according to the formulated plan.JEL Classification: O18, Q15, Q16